2019
DOI: 10.1371/journal.pone.0210702
|View full text |Cite
|
Sign up to set email alerts
|

Pelargonium sidoides radix extract EPs 7630 reduces rhinovirus infection through modulation of viral binding proteins on human bronchial epithelial cells

Abstract: Bronchial epithelial cells are the first target cell for rhinovirus infection. The course of viral infections in patients with acute bronchitis, asthma and COPD can be improved by oral application of Pelargonium sidoides radix extract; however, the mechanism is not well understood. This study investigated the in vitro effect of Pelargonium sidoides radix extract (EPs 7630) on the expression of virus binding cell membrane and host defence supporting proteins on primary human bronchial epithelial cells (hBEC). C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 48 publications
2
49
0
6
Order By: Relevance
“…These findings are not unexpected, since the efficacy of the phytopharmaceuticals examined in this study had already been demonstrated in placebo-controlled clinical trials [12][13][14][15][16] and has now been confirmed by data from actual practices. In vitro anti-infective effects have been described for various active herbal ingredients [22][23][24][25]. A possible explanation for the reduced antibiotic use following phytotherapeutic prescriptions could therefore be the occurrence of fewer bacterial sequelae of respiratory tract infections.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are not unexpected, since the efficacy of the phytopharmaceuticals examined in this study had already been demonstrated in placebo-controlled clinical trials [12][13][14][15][16] and has now been confirmed by data from actual practices. In vitro anti-infective effects have been described for various active herbal ingredients [22][23][24][25]. A possible explanation for the reduced antibiotic use following phytotherapeutic prescriptions could therefore be the occurrence of fewer bacterial sequelae of respiratory tract infections.…”
Section: Discussionmentioning
confidence: 99%
“…This herbal medicine has been experimentally proven for anti-viral activity. The commercial extract EPs 7630 ® interfered in vitro with the replication of different respiratory viruses, including human coronavirus ( Michaelis et al, 2011 ), Influenza virus ( in vitro and in vivo ) ( Theisen and Muller, 2012 ), and Rhinovirus isolated from patients with severe asthma ( Roth et al, 2019 ). EPs 7630 was able to stimulate IFN-β in vitro , and gallic acid enhanced the expression of iNOS and TNF-α ( Kolodziej et al, 2003 ).…”
Section: Resultsmentioning
confidence: 99%
“…Pelargonium sidoides (PS), the important traditional medicine for treatment of diarrhea and dysentery in South Africa, has antibacterial, antifungal, antimycobacterial, and immunomodulatory properties [13]. Moreover, PS can prevent asthma attacks during upper respiratory tract viral infections and reduce rhinovirus infection by modulating viral binding proteins [14,15]. Coptis Rhizoma (CR) is used to treat of bacillary dysentery, typhoid, tuberculosis, epidemic cerebrospinal meningitis, pertussis, and other diseases [16].…”
Section: Introductionmentioning
confidence: 99%